A Comparative Analysis of Women and Men-Owned MSMEs with Special Emphasis on Women Entrepreneurship: A Case Study of Cachar District, Assam. Issue 4 (December 2020) - Sanu, Md Sahnewaz; Ahmad, Md Firdos; Anjum, Shabana
The purpose of this research is to investigate the effect of micro, small and medium enterprises on women entrepreneurship development with particular reference to Cachar district of Assam. The study also aims to compare the characteristics and performance of women-owned MSMEs with those owned by men. A survey method is used to gather information from 200 MSME owner-managers located in various revenue circles/ tehsils of Cachar district. The results of the study indicate that, though very slowly, MSMEs are significantly promoting women entrepreneurship. The most important reasons for women entrepreneurs to join MSMEs appear to be (a) 'profit motive' or 'to earn better income', (b) 'desire for independence' and (c) 'to support family' or 'the desire to provide financial security to the family'. The results of the Kruskal Wallis test demonstrate that women entrepreneurs' background characteristics such as their marital status, age, levels of educational attainment, previous business experience and place of residence significantly affect their motivations to join MSMEs. While the employment growth in female-owned MSMEs is much higher than their male counterparts, net-return per owner-manager is found to be significantly higher in men-owned MSMEs than in women-owned MSMEs.